Malignant Glioma in the Cerebellum Presenting as Multiple Small Lesions - Takashi Mamiya; Shinji Shimato; Toshihisa Nishizawa; Takashi Yamanouchi; Kojiro Ishikawa; Makoto Ito; Masato Abe; Kyozo Kato (Case Reports in Oncological Medicine)
Malignant glioma, the most common malignant primary brain tumor in adults, usually occurs in supratentorial space as a single mass lesion, and cerebellar location and multiple appearance are uncommon. We report a case of a 69-year-old female with three lesions simultaneously found in the cerebellum on magnetic resonance images (MRIs) after suffering from gait disturbance. Two lesions were around 15 mm in size and the other one was observed as a spotty enhancement. Although MRI findings suggested brain metastases, whole body examinations denied any primary malignancies. Biopsy for one lesion in the cerebellum was performed, which resulted in pathological diagnosis of malignant astrocytoma. The lesions were considered multicentric glioma based on MRI definition. The treatment with temozolomide and whole brain radiation was completed. Although the patient was discharged in an independent state with the shrinkage of the tumors, she unexpectedly died following sudden loss of consciousness from an unknown cause one month after discharge. The coincidence of cerebellar location and multicentricity characterized by smallness is quite rare in glioma patients, and such MRI findings might be misleading for the diagnosis. We describe the details of the case and discuss the pathogenesis of this unique presentation of malignant glioma with the literatures.